Effects of hydroalcoholic extract of Ziziphus jujuba on acetic acid induced ulcerative colitis in male rat (Rattus norvegicus) - Tanideh, Nader; Jamshidzadeh, Akram; Ghanbari Saghesloo, Ali; Rahmanifar, Farhad; Mokhtari, Maral; Koohi-Hosseinabadi, Omid; Omidi, Mahmood; Najibi, Asma (Journal of Coloproctology, 2016)
Objective To investigate the effects of hydroalcoholic extract of Ziziphus jujuba on the histopathological, tissue oxidative stress and inflammation plus to antioxidant pathways of colon tissue in rat with induced Ulcerative colitis.Materials and methods Ulcerative colitis was induced in 80 rats those divided into 8 equal groups. Group 1 and 2 were negative controls receiving 1 mL/day of normal saline in enema and oral; group 3 and 4 as positive control 1 and 2 received 10 mg/kg of intra-colonic asacol and oral mesalazine; groups 5 and 6 received 20% and 40% of hydroalcoholic extract of Z. jujuba trans-rectally; group 7 and 8 received 1500 and 3000 mg/kg of hydroalcoholic extract of Z. jujuba orally, respectively. After 7 days, animals were evaluated for colon tissue histopathology, levels of malondialdehyde and IL-1β, and activities of superoxide dismutase, glutathione peroxidase and myeloperoxidase in colon tissue.Results Hydroalcoholic extract of Z. jujuba in both forms of trans-rectal and oral administration especially in the higher doses could result into a more healing effect in damaged colonic tissue, more reduce glutathione peroxidase and IL-1β level. Also, these two doses (gel 40% and oral 3000 mg/kg) could more decrease the myeloperoxidase activity and stimulate superoxide dismutase and glutathione peroxidase activities. Also, gel 40% in transrectal administration was more potent than administration 3000 mg/kg in oral.Conclusion The results of the present study indicated that Z. jujube may be considered as a treatment of choice for Ulcerative colitis especially in gel form and also in dose-dependent pattern.
Keywords: Ziziphus jujuba; Ulcerative colitis; Oxidative stress; Histopathology; Inflammation